Teachers perception about epilepsy Percepção de professores sobre epilepsia - Paula T. Fernandes; Ana L.A. Noronha; Ulisses Araújo; Paula Cabral; Ricardo Pataro; Hanneke M. de Boer; Leonid Prilipko; Josemir W. Sander; Li M. Li (Arquivos de Neuro-Psiquiatria)
PURPOSE: To identify in a town of Brazil the knowledge, attitude and perception of epilepsy in teachers of elementary schools and to compare these before and after a training exercise. METHODS: Teachers of nine public schools of Barão Geraldo, Campinas, Brazil completed a questionnaire. Two researchers had meetings with teachers, presenting the Global Campaign "Epilepsy out of the shadows", when the questionnaire was first completed by all attendees. Twenty teachers of these schools were motivated to attend a training course entitled "Epilepsy and Health" as part of their continuous education programme. Two years later the same questionnaire was again completed (post-test) by these 20 teachers. RESULTS: 100 teachers originally completed the questionnaire (97 women, mean age 42 years, 64 married). Forty-three percent of teachers said that they had enough knowledge regarding epilepsy and 20% said that they had poor knowledge about the condition. Regarding the IQ of children with epilepsy, 45% of teachers believed that they had average IQ, 18% above average, six percent under average and 29% did not know. Teachers believed that children with epilepsy have a higher possibility of acquiring mental disease in the future (51%); that epilepsy is a disease (68%); that epilepsy is contagious (1%); epilepsy is treatable (90%). After the course, the teachers’ beliefs seem to have improved. DISCUSSION: This work with elementary school teachers identified difficulties related to epilepsy which, if addressed, may help promote better quality of life of people with epilepsy in the community and help to decrease stigma attached to the condition. Better informed teachers are likely to have a more positive attitude and this will be passed to others. Educational campaigns about epilepsy amongst teachers should be encouraged as this may improve the management of epilepsy, by helping to develop a well informed and tolerant community. OBJETIVO: Identificar atitudes e percepção dos professores do ensino fundamental a respeito da epilepsia, antes e depois de um curso específico sobre o tema. MÉTODO: Participaram da pesquisa professores de nove escolas da rede pública do ensino fundamental de Barão Geraldo, distrito de Campinas, SP. Dois pesquisadores reuniram-se com os professores e apresentaram a Campanha Global "Epilepsia fora das sombras", momento também em que os questionários foram aplicados. Vinte professores ficaram motivados para fazer o curso de extensão "Temas transversais: epilepsia e saúde". Após este curso, os questionários foram re-aplicados. RESULTADOS: Foram aplicados 100 questionários em professores das nove escolas, sendo que: noventa e sete professores eram do sexo feminino, idade média de 42 (D.P. 22 a 63) e 64 estavam casados. Quarenta e três professores declararam possuir conhecimento sobre epilepsia abaixo da média e 20, disseram possuir um pobre conhecimento sobre a condição. No que diz respeito à idéias sobre epilepsia, os professores acham que: as crianças com epilepsia tem QI igual (45%), na média (18%), abaixo da média (6%) e não sabem opinar (29%); crianças com epilepsia têm maior chance de terem doença mental no futuro (51%); a epilepsia é uma doença (68%); a epilepsia é contagiosa (1%); a epilepsia é tratável (90%). Após o curso, crenças e mitos sobre epilepsia dos professores mostraram diferenças significativas. DISCUSSÃO: Idéias errôneas sobre epilepsia podem ser mudadas através de cursos educacionais sobre epilepsia. Este trabalho, realizado com professores do ensino fundamental, visou a identificação das dificuldades relacionadas à epilepsia para promover a redução do estigma. É importante que professores sejam melhor instruídos sobre a epilepsia para consequentemente, ter atitudes mais positivas em relação às crianças com epilepsia. Acreditamos que professores mais capacitados melhoram a maneira de lidar e de se relacionar com crianças com epilepsia, para a construção de uma comunidade bem informada e mais tolerante para lidar com as diferenças.